Length Matters: Informational Load in Ambiguity Resolution - Barbara Hemforth; Saveria Colonna; Caterina Petrone; Mariapaola D’Imperio (Discours, 2013)
In this paper, we will compare prosodic and pragmatic approaches to the role of constituent length in attachment ambiguities. Lengthening a constituent affects its informativity: longer constituents are usually less predictable (Levy & Florian, 2007) and demand a higher processing load than shorter ones (Almor, 1999). Following neo-Gricean accounts (Levinson, 1987 and 1991), increased informational load needs to be justified. This justification is achieved more easily when the long constituent conveys new information and when it relates to central elements of the utterance. Informational load is, however, not a simple question of length in numbers of characters or syllables but more likely a question of amount of information. In three off-line experiments using a cloze task, we will compare the effect of lengthening ambiguous prepositional phrases as in [1a/b/c] either by lengthening a city name or by adding information about the city. We will show that only lengthening by adding information increases attachment to a more central element of the utterance. These results will be discussed based on prosodic and pragmatic factors explaining the role of constituent length for attachment ambiguities.[1] Peter met the doctor of the lawyer from a. Apt. / b. Aix-en-Provence / c. the beautiful city of Apt.